Financial distress analysis of PT Sepatu Bata, Tbk listed on the Indonesia Stock Exchange - Santoso, Cahyo Budi; lstiningrum, Rr. Farida; Prihartanti, Wiwik; Gamal, Ahmad (Enrichment : Journal of Management, 2024)
This study aims to determine the development of business at PT Sepatu Bata, Tbk by looking at secondary data in the form of financial statements from 2017 to 2022. The technique used in this study is to use the Altman Z-Score method where if the Z value is more than 2.99 it is classified as a healthy company. If the Z value is less than 1.81, it is classified as an unhealthy company. If the Z value is between 1.81 and 2.99, it is classified as a company in the grey area or vulnerable area. From the results of research that has been conducted from 2017 to 2021 based on financial statements, it is known that PT Sepatu Bata, Tbk has a Z value> 2.99, which means that the company is in good health, but in 2022 it actually experienced financial distress because the Z value < 1.81 or in other words the company can be classified as a company experiencing financial distress.